Assessment of the genotoxic and carcinogenic potentials of 3‐aminothiophene derivatives using in vitro and in silico methodologies. Issue 7 (11th October 2013) - Lepailleur, Alban; Bureau, Ronan; Halm‐Lemeille, Marie‐Pierre; Bouquet, Michel; Pecquet, Régis; Paris‐Soubayrol, Christine; Goff, Jérémie Le.; André, Véronique; Lecluse, Yannick; Lebailly, Pierre; Maire, Marie‐Aline; Vasseur, Paule
ABSTRACT Thiophene derivatives, a class of compounds widely used in products such as pharmaceuticals, agrochemicals or dyestuffs, represent chemicals of concern. Indeed, the thiophene ring is often considered as a structural moiety that may be involved in toxic effects in humans. We primarily focus on the genotoxic/mutagenic and carcinogenic potentials of the methyl 3‐amino‐4‐methylthiophene‐2‐carboxylate (1), a precursor of the articaine local anesthetic (4) which falls within the scope of the European REACH (Registration, Evaluation, Authorisation and restriction of CHemicals) legislation. To discern some structure–toxicity relationships, we also studied two related compounds, namely the 3‐amino 4‐methylthiophene (2) and the 2‐acetyl 4‐chlorothiophene (3). Techniques employed to assess mutagenic and DNA‐damaging effects involved the Salmonella mutagenicity assay (or Ames test) and the single‐cell gel electrophoresis assay (or Comet assay). In the range of tested doses, none of these derivatives led to a positive response in the Ames tests and DNA damage was only observed in the Comet assay after high concentration exposure of 2. The study of their carcinogenic potential using the in vitro SHE (Syrian Hamster Embryo) cell transformation assay (CTA) highlighted the activity of compound 2. A combination of experimental data with in silico predictions of the reactivity of thiophene derivatives towards cytochrome P450 (CYP450), enabled us to hypothesize possible pathways leading to these toxicological profiles. Copyright © 2013 John Wiley & Sons, Ltd.